Micro-computed tomography analysis of mineral attachment to the implants augmented by three types of bone grafts: An experimental study in dogs - Mahdi Gholami; Farzaneh Ahrari; Hamideh Salari Sedigh; Christoph Bourauel (Wolters Kluwer Medknow Publications, 2023)
Background: This study compared the effect of various grafting materials on the area and volume of minerals attached to dental implants. Materials and Methods: In this animal study, 13 dogs were divided into three groups according to the time of sacrificing (2 months, 4 months, or 6 months). The implants were placed in oversized osteotomies, and the residual defects were filled with autograft, bovine bone graft (Cerabone), or a synthetic substitute (Osteon II). At the designated intervals, the dogs were sacrificed and the segmented implants underwent micro-computed tomography analysis. The bone-implant area (BIA) and bone-implant volume (BIV) of bone and graft material were calculated in the region of interest around the implant. The data were analyzed by two-way analysis of variance (ANOVA) at P < 0.05. Results: There was no significant difference in BIA and BIV between the healing intervals for any of the grafting materials (P > 0.05). ANOVA exhibited comparable BIA and BIV between the grafting materials at 2 and 4 months after surgery (P > 0.05), although a significant difference was observed after 6 months (P < 0.05). Pairwise comparisons revealed that BIA was significantly greater in the autograft-stabilized than the synthetic-grafted sites (P = 0.035). The samples augmented with autograft also showed significantly higher BIV than those treated by the xenogenic (P = 0.017) or synthetic (P = 0.002) particles. Conclusion: All graft materials showed comparable performance in providing mineral support for implants up to 4 months after surgery. At the long-term (6-month) interval, autogenous bone demonstrated significant superiority over xenogenic and synthetic substitutes concerning the bone area and volume around the implant.